1889 N.Y. Laws 167, ch. 140 § 2 - (:unkn) unknown (General Publisher, 1889)
Prohibited using, intent to use, or carrying concealed any slung-shot, billy, sand-club, metal knuckles, dagger, dirk, dangerous knife. Violators guilty of a felony.
--
Keywords: POSSESSION - NON-GUN ARMS